Inside the Carnival : Unmasking Louisiana Politics - Parent, Wayne, 1955- (Book collections on Project MUSE., 2004)
"Wayne Parent's main theme is that Louisiana's ethnic mix, natural resources, and geography define a culture that in turn produces its unique political theater. He gives special attention to immigration patterns and Louisiana's abundant supply of oil and gas, as well as to the fascinating variations in political temperaments in different parts of the state. Most important, he delivers thorough and concise explanations of Louisiana's unusual legal system, odd election rules, overwrought constitutional history, convoluted voting patterns, and unmatched record of political corruption - while also noting signs of change in the offing."--Jacket.